Adipokines in Peritoneal Dialysis: Relevant Clinical Impact According to Body Composition. Issue 2 (3rd November 2014) - Bernardo, Ana Paula; Fonseca, Isabel; Oliveira, José Carlos; Santos, Olivia; Carvalho, Maria João; Cabrita, António; Rodrigues, Anabela
Abstract Adipokines impact on clinical outcomes is not adequately addressed in peritoneal dialysis (PD). We investigated the impact of leptin/adiponectin ratio (L/A) as a predictor of cardiovascular events (CVE) in PD, taking into consideration patient's body composition and the potential role of glucose load. We prospectively followed 66 prevalent PD patients for 47.0 ± 28.2 months. New CVE were evaluated. Lean tissue index (LTI), relative fat mass (relFM) and relative overhydration (relOH) using multifrequency bioimpedance (BCM) were assessed; serum lipids, interleukin‐6 (IL‐6), leptin and adiponectin were measured. We established the determinants of L/A using multiple linear regression and the impact of L/A on CVE. Obesity was present in 47 (73.4%) patients according to relFM, and in seven (10.6%) according to body mass index (BMI). Leptin and L/A exhibited a stronger correlation with relFM (both r = 0.62, P < 0.0001) than with BMI (r = 0.46 and r = 0.51, respectively, both P < 0.0001). L/A showed a significant correlation with triglycerides (r = 0.41, P = 0.001) and HDL‐cholesterol (r = −0.358, P = 0.003), better than isolated leptin or adiponectin. RelFM (RR = 0.130, 95%confidence interval [CI]:0.086–0.174, P < 0.0001) and LTI (RR = 0.194, 95%CI:0.037–0.351, P = 0.016) were independent predictors of L/A (R2 = 0.67). Patients who suffered new CVE were older (59.12 ± 12.41 vs. 47.52 ± 13.84years, P = 0.003) and had a higher relOH (11.28 ± 7.29 vs. 6.60 ± 8.16%, P = 0.028). L/A was significantly higher in patients with CVE[2.29 (1.79) vs. 0.65 (1.73), P = 0.028] but this association was only put on evidence after excluding patients with wasting. BMI is an inaccurate method to classify obesity in PD since it underestimates its prevalence compared with body composition assessment using BCM. High adiponectin and low leptin are associated with a more favorable metabolic risk profile in peritoneal dialysis. The L/A is determined by relFM and by LTI. A higher L/A is associated with CVE in PD patients without wasting.